Compostos bioativos e atividade antioxidante em polpas de mangaba (Hancornia speciosa Gomes) in natura e processada, em pó liofilizado e reidratada - Rocha, Katiúscia Ramos Alves (2015)
In the state of Sergipe, mangaba is one of the most abundant and sought fruit consumed as frozen pulp, juice and ice cream. One way of conservation of fruit and maintenance of chemical, nutritional and organoleptic characteristics, is the lyophilization process. Given the importance of mangaba for the state of Sergipe, the bioactive compounds and antioxidants important for health and present in mangaba, the aim of this study was to determine these compounds (vitamin C, carotenoids, phenolic compounds, organic acids) and the antioxidant activity ( DPPH, ABTS and FRAP), present in the pulp of raw and pasteurized mangaba, dry powder and rehydrated. By colorimetry, confirmed the high vitamin C content of mangaba. Spectrometry, it was determined low concentrations of carotenoids. Further phenolic and flavonoid concentrations in samples of fresh pulp to pulp in the pasteurized samples. Through high performance liquid chromatography (HPLC) were identified and quantified the main organic acids (citric acid, L-ascorbic acid and D-malic and fewer D-tartaric acid), phenolic compounds (rutin, quercetin and chlorogenic acid ), and the β-carotene content in the samples showed higher pulp in natura that in their respective samples of pasteurized pulp. The antioxidant activities, the highest concentrations were determined in samples of pulp in natura for DPPH and ABTS radical and in pasteurized pulp samples through the FRAP method. Given the above results, the mangaba has higher or lower concentrations of all bioactive compounds and antioxidant activities studied, so the consumption of mangaba and the production of by-products should be encouraged.